(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2024)
As an area that has quite diverse tourism potential, the Tidore Islands City government does not yet have a clear and focused concept in developing this superior tourist destination in order to boost the development of a sustainable tourism sector based on local potential in the Tidore Islands City. The research results show that the number of plants or vegetation that grow and are identified in the Akesahu tourist attraction area is 282 vegetation consisting of 19 types or species. Based on the data obtained, the banana plant (musa paradisiaca) is the most commonly found species, namely 104 trees. Meanwhile, the fewest species found were hibiscus (hibiscus tiliaceus), areca nut (areca catechu), and banyan tree (ficus benjamina), each numbering 1. Apart from that, 2 types of mangroves were also found growing in the Akesahu tourist area, namely avicennia lanata and bruguiera gymnorrhiza. However, several infrastructure facilities are in a damaged condition and have not been repaired. This is caused by the minimal budget allocated. Apart from building tourism infrastructure, the Tidore City government is also aggressively promoting tourism through activities on a national and international scale such as the Sail Tidore event in 2022 and hosting Archipelago Day in 2023. Apart from that, local scale events are also carried out as an effort to promote and introduce culture. as well as tourism in Tidore City, which is collaboratively carried out by the regional government and existing local communities.